APLIKASI MANAJEMEN RISIKO PADA PROYEK JALAN TOL SEMARANG-SOLO RUAS BAWEN-SOLO - Nurdiana, Asri; Setiabudi, Bambang (Jurnal Proyek Teknik Sipil, 2018)
At construction project there must be risks. Risk is a consequence of the uncertainty conditions. In construction projects, the risk can’t be predicted as well because there are a lot of uncertainty to predict problems (Nurdiana, 2015). The aims of this paper are to identify the risk from contractor persepction; to analyze the risk from contractor persepction; and to assign the risk respon from contractor persepction at project of Semarang-Solo Highway (segment Bawen-Solo).The primary data were the identification of risk and the assessment of risk (probability and impact of risk) that obtained by interview and questionnaire method. The secondary data were the project document and the previous research. Data analysis was done by Risk Breakdown Structure method.The identification of risks in the Bawen-Solo Highway project is divided into 4 categories, that are technical risk, procurement risk, contractual risk, and managerial risk. The risk identification is 11 risks which are in the risk category above. Based on the risk analysis that has been done, the biggest risk is contractual risk, which is the contract termination due to project delay. From the value of risk that has been analyzed, the majority of risk is at a low risk level (86%), then moderate risk (14%). Based on an analysis of the risk response, 86% of the risk response is accepted, and 14% of the risk response is mitigation.